Effectiveness of Solid Antibacterial Soap Formulated with Green Mussel Shell Waste (Perna viridis) against Staphylococcus aureus - Belvan Adzin Muyassar Muyassar; Joko Santoso; Ediati Sasmito (Universitas Wahid Hasyim Semarang, 2026)
Staphylococcus aureus is a major cause of skin infections and remains a public health concern due to its high prevalence and the increasing emergence of antibiotic-resistant strains such as methicillin-resistant S. aureus (MRSA). These conditions highlight the importance of preventive approaches using non-antibiotic topical products. This study aimed to evaluate the antibacterial effectiveness of solid soap formulated with green mussel shell powder (Perna viridis), as well as its physical quality and consumer acceptance. A true experimental posttest-only control group design was applied using five formulations: F I (2%), F II (4%), F III (6%), F IV (0%, negative control), and F V (benzalkonium chloride as positive control). Antibacterial activity was assessed using the disc diffusion method, and the data were analyzed using one-way ANOVA. The results showed a concentration-dependent antibacterial effect, with higher concentrations of green mussel shell powder producing greater inhibition against S. aureus. All formulations met physical quality standards and demonstrated good stability and homogeneity. Sensory evaluation indicated high consumer acceptance across all formulations. Overall, these findings suggest that green mussel shell powder has strong potential as a sustainable and effective antibacterial ingredient for solid soap formulations intended for preventive skin hygiene